2022
DOI: 10.3389/fimmu.2022.840399
|View full text |Cite
|
Sign up to set email alerts
|

Methylome and Transcriptome-Based Integration Analysis Identified Molecular Signatures Associated With Meningitis Induced by Glaesserella parasuis

Abstract: Glaesserella parasuis (G. parasuis) can elicit serious inflammatory responses and cause meningitis in piglets. Previous epigenetic studies have indicated that alterations in host DNA methylation may modify the inflammatory response to bacterial infection. However, to date, genome-wide analysis of the DNA methylome during meningitis caused by G. parasuis infection is still lacking. In this study, we employed an unbiased approach using deep sequencing to profile the DNA methylome and transcriptome from G. parasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…We confirmed a strong inflammatory response characterized by high expression of inflammatory cytokines in skeletal muscle due to G. parasuis infection. This finding aligns with the well-known predilection sites of G. parasuis infection, such as the lung, arthrosis, pleura, peritoneum, kidney, and meninges [ 42 , 43 , 44 ]. It has been reported that G. parasuis breaks through the lung’s immune defense [ 45 ], allowing it to colonize various parts of the body, including skeletal muscle, through the bloodstream.…”
Section: Discussionsupporting
confidence: 86%
“…We confirmed a strong inflammatory response characterized by high expression of inflammatory cytokines in skeletal muscle due to G. parasuis infection. This finding aligns with the well-known predilection sites of G. parasuis infection, such as the lung, arthrosis, pleura, peritoneum, kidney, and meninges [ 42 , 43 , 44 ]. It has been reported that G. parasuis breaks through the lung’s immune defense [ 45 ], allowing it to colonize various parts of the body, including skeletal muscle, through the bloodstream.…”
Section: Discussionsupporting
confidence: 86%
“…The G. parasuis SH0165 strain, serotype 5, a high virulent isolate, was isolated from a commercial pig lung with arthritis, fibrinous polyserositis, hemorrhagic pneumonia, and meningitis [1]. The SH0165 strain was grown in tryptic soy broth (TSB) (Difco laboratories, Detroit, MI, USA) or tryptic soy agar (TSA) (Difco laboratories, Detroit, MI, USA) at 37 • C, with 10 µg/mL of nicotinamide adenine dinucleotide (NAD) (Sigma, St.Louis, MO, USA) and 10% fetal bovine serum (FBS) (Gibco, Grand Island, NY, USA).…”
Section: Bacterial and Animalsmentioning
confidence: 99%
“…Glaesserella parasuis (G. parasuis), a Gram-negative bacterium, colonizes the upper respiratory tract of swine and is the etiological agent of Glässer's disease [1]. The typical characteristic of this disease is fibrinous, meningitis, and polyserositis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Glaesserella parasuis ( G. parasuis , GPS), which causes meningitis, polyserositis, arthritis, and frequently pneumonia-like symptoms, is the etiological agent of Glässer’s disease in pigs [ 1 ]. Meningitis is the most characterized symptom of this disease [ 2 ]. Infection with G. parasuis always results in high morbidity and mortality and leads to significant economic losses for the pig industry [ 3 ].…”
Section: Introductionmentioning
confidence: 99%